1977
DOI: 10.7326/0003-4819-86-4-394
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in the CREST Syndrome Variant of Progressive Systemic Sclerosis (Scleroderma)

Abstract: Severe pulmonary hypertension without pulmonary fibrosis occurred in 10 patients with the CREST syndrome (calcinosis, Raynaud's phenomenon, esophageal dysfunction, sclerodactyly, telangiectasia), reputedly a benign variant of progressive systemic sclerosis. Time from the initial symptom, Raynaud's phenomenon, to the recognition of pulmonary hypertension was as long as 40 years. Pulmonary hypertension and increased pulmonary vascular resistance was shown in all patients. Autopsy examination in three of six deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0
1

Year Published

1979
1979
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(78 citation statements)
references
References 28 publications
1
76
0
1
Order By: Relevance
“…Serum complement levels are generally normal. In immunohistologic studies, investigators have demonstrated immunoglobulin deposition in the glomeruli and the interlobular arteries of patients with PSS and renal involvement (15), as well as in the pulmonary vasculature of some patients (16). However, numerous studies (3,17) of the skin of PSS patients have failed to identify such deposits at either the dermal-epidermal junction or in the dermal vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum complement levels are generally normal. In immunohistologic studies, investigators have demonstrated immunoglobulin deposition in the glomeruli and the interlobular arteries of patients with PSS and renal involvement (15), as well as in the pulmonary vasculature of some patients (16). However, numerous studies (3,17) of the skin of PSS patients have failed to identify such deposits at either the dermal-epidermal junction or in the dermal vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Single serum samples from 92 patients with PSS were examined; the group included 68 women and 24 men, ranging in age at study from 18 to 85 years (mean 48.3). Forty-eight of these individuals (32 women, 16 phenomenon, esophageal dysfunction, sclerodactyly, and telangiectasia) variant of PSS (3). The median duration of disease was 3.4 years (1.3 years in the patients with diffuse scleroderma and 13.4 years in those with the CREST syndrome).…”
Section: Methodsmentioning
confidence: 99%
“…The most common type of involvement is cor pulmonale secondary to pulmonary hypertension. Patients with the CREST syndrome may have either a mild and prolonged course (7)(8)(9) or a progressive course with pulmonary and GI involvement (9). Death usually results from pulmonary hypertension and cor pulmonale (9).…”
Section: Discussionmentioning
confidence: 99%
“…Although myocardial involvement, hypertension, and pulmonary fibrosis can also occur in scleroderma generally, and CREST in particular, pulmonary hypertension can occur independently (Botstein and LeRoy, 1981;Bulkley et al, 1976;Gaffrey et al, 1982;Salerni et al, 1977;Smith er al., 1979;Trell and Lindstrom, 1971;Young and Mark, 1978). Pulmonary hypertension frequently leads to progressive right heart failure and death (Salemi et a]., 1977).…”
Section: Discussionmentioning
confidence: 99%